2022
DOI: 10.1021/acs.chemmater.2c00241
|View full text |Cite
|
Sign up to set email alerts
|

A Structure–Activity Study of Aromatic Acid Modulators for the Synthesis of Zirconium-Based Metal–Organic Frameworks

Abstract: Acid modulation is among the most widely employed methods for preparing metal–organic frameworks (MOFs) that are both stable and highly crystalline, yet there exist few guiding principles for selecting the optimal modulator for a given system. Using the Zr-based MOFs UiO-66 and UiO-68-Me2 (UiO = Universitetet i Oslo) as representative materials, here we present for the first time an in-depth structure–activity study of acid modulators and identify key principles of modulation for the synthesis of highly crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 56 publications
8
68
0
Order By: Relevance
“…For Form 1, a gradual broadening of the reflections due to a decrease in crystallinity was observed above 50 equiv., which is not expected given the increase in crystallinity that is generally observed when higher equivalents of acid modulators are employed. 25,29,35 In contrast, the crystallinity of Form 2 increased with increasing equivalents of FA, as expected. Because the role of acid modulators is generally to enhance the reversibility of MOF formation, 25 we hypothesize that Form 1 is a kinetic phase whereas Form 2 is the thermodynamically favored phase.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…For Form 1, a gradual broadening of the reflections due to a decrease in crystallinity was observed above 50 equiv., which is not expected given the increase in crystallinity that is generally observed when higher equivalents of acid modulators are employed. 25,29,35 In contrast, the crystallinity of Form 2 increased with increasing equivalents of FA, as expected. Because the role of acid modulators is generally to enhance the reversibility of MOF formation, 25 we hypothesize that Form 1 is a kinetic phase whereas Form 2 is the thermodynamically favored phase.…”
Section: Resultssupporting
confidence: 80%
“…25,29,35 In contrast, the crystallinity of Form 2 increased with increasing equivalents of FA, as expected. Because the role of acid modulators is generally to enhance the reversibility of MOF formation, 25 we hypothesize that Form 1 is a kinetic phase whereas Form 2 is the thermodynamically favored phase. Consistently, postsynthetic treatment of Form 1 with excess FA converted it to Form 2, as confirmed by PXRD (SI Figure S29).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…72,74 Later on, the role of modulators was investigated in the synthesis of other MOFs such as the most stable Zr-MOFs (UiO-66, UiO-66–NH 2 , UiO-67, and UiO-68–NH 2 ). 32,75 In these MOFs, strong interactions between six zirconium cations in a square-antiprismatic geometry by bridging μ 3 -O and μ 3 -O –OH with twelve di-carboxylic groups of the ligands make very stable structures. It was indicated that acid modulators ( e.g.…”
Section: Design and Synthesis Of Defectsmentioning
confidence: 99%